Ecological Diversification of Vibrio fischeri Serially Passaged for 500 Generations in Novel Squid Host Euprymna tasmanica - Soto, William (2014)
Vibrio fischeri isolated from Euprymna scolopes (Cephalopoda: Sepiolidae) was used to create twenty-four lines that were serially passaged through the non-native host E. tasmanica for 500 generations. These derived lines were characterized for biofilm formation, swarming motility, carbon source utilization, and in vitro bioluminescence. Phenotypic assays were compared between “ES” (E. scolopes) and “ET” (E. tasmanica) V. fischeri wild isolates to determine if convergent evolution was apparent between E. tasmanica evolved lines and ET V. fischeri. Ecological diversification was observed in utilization of most carbon sources examined. Convergent evolution was evident in motility, biofilm formation, and select carbon sources displaying hyperpolymorphic usage in V. fischeri. Convergence in bioluminescence (a 2.5-fold increase in brightness) was collectively evident in the derived lines relative to the ancestor. However, dramatic changes in other properties—time points and cell densities of first light emission and maximal light output and emergence of a lag phase in growth curves of derived lines suggest increased light intensity per se was not the only important factor. Convergent evolution implies gnotobiotic squid light organs subject colonizing V. fischeri to similar selection pressures. Adaptation to novel hosts appears to involve flexible microbial metabolism, establishment of biofilm and swarmer V. fischeri ecotypes, and complex changes in bioluminescence. Our data demonstrate numerous alternate fitness optima or peaks are available to V. fischeri in host adaptive landscapes, where novel host squids serve as habitat islands. Thus, V. fischeri founder flushes occur during the initiation of light organ colonization that ultimately trigger founder effect diversification.